PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEDISIPLINAN PEGAWAI DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TAKALAR - Nur Firman; Nuryanti Mustari; Nurbiah Tahir (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2020)
This study aimed to determine and analyze the influence of transformational leadership style on employee discipline in the Office of Population and Civil Registry of Takalar Regency. This study used a descriptive study using quantitative methods and approaches that described the transformational leadership style of employee discipline in the Office of Population and Civil registry of Takalar Regency. The population in this study were all employees in the Office of Population and Civil Registry of Takalar regency as many as 50 people, civil servants were 30 people and 20 honorary. Sampling technique used saturated sampling. The results showed that the transformational leadership style had a positive and significant effect on employee discipline at the Office of Population and Civil Registration, with an R square coefficient of 0,524, meaning 52.4% of the leadership style affected employee discipline at the Office of Population and Civil Registration at Takalar Regency.